Critical undrained shear strength of sand-silt mixtures under monotonic loading - Mohamed Bensoula; Hanifi Missoum; Karim Bendani (Earth Sciences Research Journal)
This study uses experimental triaxial tests with monotonic loading to develop empirical relationships to estimate undrained critical shear strength. The effect of the fines content on undrained shear strength is analyzed for different density states. The parametric analysis indicates that, based on the soil void ratio and fine content properties, the undrained critical shear strength first increases and then decreases as the proportion of fines increases, which demonstrates the influence of fine content on a soil’s vulnerability to liquefaction. A series of monotonic undrained triaxial tests were performed on reconstituted saturated sand-silt mixtures. Beyond 30% fines content, a fraction of the silt participates in the soil’s skeleton chain force. In this context, the concept of the equivalent intergranular void ratio may be an appropriate parameter to express the critical shear strength of the studied soil. This parameter is able to control the undrained shear strength of non-plastic silt and sand mixtures with different densities.